Clinical efficacy of bladder hydrodistension combined with oral mirabegron and intravesical instillation in the treatment of interstitial cystitis - Lei Du; Ziyue Ma; Wenyong Xue; Wei Li (Pakistan Journal of Medical Sciences, 2026)
Objective: To evaluate the therapeutic efficacy of bladder hydrodistension combined with oral mirabegron and intravesical instillation in patients with interstitial cystitis(IC). Methodology: This was a retrospective study. Ninety patients diagnosed with IC at The Second Hospital of Hebei Medical University between October 2023 to October 2025 were retrospectively enrolled and randomized into two groups(n=45 each). All participants underwent cystoscopic examination followed by bladder hydrodistension. Patients in the control group received oral mirabegron sustained-release tablets in conjunction with hydrodistension. In addition to the same regimen, patients in the study group were administered sodium hyaluronate via intravesical instillation. The treatment duration for both groups was six months. Clinical symptom improvement and clinical efficacy were assessed at the end of treatment. Results: After six months of treatment, scores on the Pelvic Pain and Urgency/Frequency Patient Symptom Scale, Interstitial Cystitis Symptom Index, and Interstitial Cystitis Problem Index were significantly lower in the study group than in the control group(p= 0.00, respectively). The overall response rate was higher in the study group compared with the control group(p= 0.03). Patients receiving the triple therapy exhibited a greater reduction in both daytime voiding frequency and nocturia episodes(p= 0.00, respectively), together with a significantly increased maximum bladder capacity(p= 0.00). Conclusion: The combination of bladder hydrodistension, oral mirabegron, and intravesical instillation demonstrates superior clinical benefit in patients with IC. This regimen can enhance symptom relief, decrease urinary frequency, expand bladder capacity, and reduce urinary levels of EGF, NGF, and IGF-1 without a significant increase in adverse events.